Is the National Patient Safety Agency (NPSA) alert 20 risk assessment tool appropriate for use in a paediatric hospital?. Issue 4 (11th March 2011) - Isaac, R; Correa, J
Abstract : Objectives: Using injectable drugs in children may pose different risks compared to use in adults. Does scoring the therapeutic risks for children alter the injectable risk priorities in a children's hospital? Methods: Local medication incident reports, medicines information queries, pharmacist interventions and local policies containing medication were searched and accessed if injectable medications were cited. The results were put into 11 categories (BCH risk tool). Each injectable product was assessed according to BCH risk tool and a score assigned. The BCH risk tool score was multiplied by the National Patient Safety Agency (NPSA) risk assessment score to achieve a combined risk tool. Each list was ranked and compared. The highest combined risk list was cross referenced with national IV guide (Medusa) as to suitability for children. Results: 712 injectable products were listed on the pharmacy computer. The primary route the product is used in BCH is shown in table below: 203 of theintravenous route can be given either as bolus or infusion and 53 of the IM/ SC injection can be given intravenously. Different information for administration would be required. Over 52% of the injectable products scored four or more of the BCH risk elements. BCH risk elements included being unlicensed (27.7%); extravasation risk (38.5%), narrow therapeutic index (21.9%), original product containing five times the dose for a 10 kg child (28.4%) and technical information for adult or package insert causing harm to a child (14.6%). 14.4% were considered high risk using the NPSA risk tool. Almost a third of these would become moderate risk if part vial not required, and a further nine products if a weight based calculation was not required. 562 injectables needed part vials in children, compared with 22 of the 562 in adults. Needing to perform a complex calculation was a risk in 33 products for adults out of 197 required in a paediatric preparation. 203 different injectables were considered a risk using the BCH risk tool, but scored moderate or low risk using the NPSA tool. 24% of the BCH high risk injectables did not have a monograph available on Medusa for adult or child. Medusa was not appropriate for 79.6% injectables on the BCH top 54 risk list, the user was not alerted to the unsuitability for a child in the monograph. Conclusion: In children, therapeutic risks of injectables should be scrutinised and assigned a weighted score compared to adults. Injectable drugs in children present a higher preparation risk compared to adults, often due to the need to use portions of the container or increased use of calculations. The national IV guide does not provide sufficient technical information to provide safe use of injectable medicine for the paediatric population. Paediatric specific information should be added.